HcZnT2 is a highly mycorrhiza-induced zinc transporter from Hebeloma cylindrosporum in association with pine - Ho-Plágaro, Tania; Usman, Muhammad; Swinnen, Janne; Ruytinx, Joske; Gosti, Françoise; Gaillard, Isabelle; Zimmermann, Sabine D. (Frontiers in Plant Science, 2024)
Zinc (Zn) shortage is a common micronutrient deficiency affecting plants worldwide, while Zn toxicity may occur when this metal is in excess. Ectomycorrhizal (ECM) fungi are known to be able to modulate the transfer of macro-and microelements, among them Zn, to the plant. However, the underlying mechanisms are not well understood. We identified the HcZnT2 gene from the ECM fungus Hebeloma cylindrosporum, encoding a member of the Cation Diffusion Facilitator (CDF) family including Zn transporters, and analyzed its transcriptional regulation, the transport function by yeast complementation experiments, and its subcellular localization using a GFP fusion protein in yeast. HcZnT2 is highly induced during mycorrhization of Pinus pinaster, and upregulated in presence of the host plant root even without any direct contact. However, HcZnT2 is repressed by Zn excess conditions. By functional expression in yeast, our results strongly support the ability of HcZnT2 to transport Zn and, to a lesser extent, manganese. HcZnT2 localization was associated with the endoplasmic reticulum of yeast. Mycorrhizal gene activation at low external Zn suggests that the Zn transporter HcZnT2 might be important for the early establishment of the ECM symbiosis during Zn deficiency, rather than under Zn excess. HcZnT2 arises as an extremely remarkable candidate playing a key role in Zn homeostasis and regulation in ectomycorrhiza.